Histomorphological and Immunohistochemical Study of Extra Nodal Lymphoma - Vani, B R; N, Sandhyalakshmi B; Sajjan, Netra M; C, Panduranga; B, Deepak Kumar; V, Srinivasamurthy (Annals of Pathology and Laboratory Medicine, 2021)
Background: NHL are heterogeneous group of hematolymphoid malignancy occurring in nodal and extra nodal sites. Extra nodal lymphoma (ENL) is distinct from nodal lymphomas due to varied anatomical location, morphological diversity. Methods: A retrospective observational study was conducted in the department of pathology from January 2011 till December 2019. Clinical details and other investigations were recorded. Gross morphological features were noted. Slides are reviewed microscopically and blocks were subjected to IHC for further typing cases were selected as per Dawson et al criteria. Result: During study period, ENL constituted 25 cases (29.4%) of the 85 cases of all NHL. Age range is 05 to 63 years with a mean age of 42.5 years. Male to female ratio is 2.2 :1.Head and neck is the most common site of ENHL constituting 19 cases(76%), next commonest location is in the GIT with 3 cases (12%). We had one each case of ENHL in testis, breast and spine (4% each). On IHC, 92% cases (23 cases) exhibited B cell phenotype and the remaining 08 % (02 cases) were of T cell phenotype. Conclusion: Lymphomas in the extra nodal sites are rare but has the propensity to occur in any anatomic site. Hence a differential of lymphoma to be considered in extra nodal site. Histology with IHC enables to differentiate from poorly differentiated carcinoma as the treatment modalities and prognosis varies.